Comprehensive screening strategy coupled with structure-guided engineering of l-threonine aldolase from Pseudomonas putida for enhanced catalytic efficiency towards l-threo-4-methylsulfonylphenylserine - Li, Lihong; Zhang, Rongzhen; Xu, Yan; Zhang, Wenchi (Frontiers in Bioengineering and Biotechnology, 2023)
l-Threonine aldolases (TAs) can catalyze aldol condensation reactions to form -hydroxy--amino acids, but afford unsatisfactory conversion and poor stereoselectivity at the C position. In this study, a directed evolution coupling high-throughput screening method was developed to screen more efficient l-TA mutants based on their aldol condensation activity. A mutant library with over 4000 l-TA mutants from Pseudomonas putida were obtained by random mutagenesis. About 10% of mutants retained activity toward 4-methylsulfonylbenzaldehyde, with five site mutations (Ala9Leu, Tyr13Lys, His133Asn, Glu147Asp, and Tyr312Glu) showing higher activity. Iterative combinatorial mutant A9V/Y13K/Y312R catalyzed l-threo-4-methylsulfonylphenylserine with a 72% conversion rate and 86% diastereoselectivity, representing 2.3-fold and 5.1-fold improvements relative to the wild-type. Molecular dynamics simulations illustrated that additional hydrogen bonds, water bridge force, hydrophobic interactions, and -cation interactions were present in the A9V/Y13K/Y312R mutant compared with the wild-type to reshape the substrate-binding pocket, resulting in a higher conversion and C stereoselectivity. This study provides a useful strategy for engineering TAs to resolve the low C stereoselectivity problem and contributes to the industrial application of TAs.